Positive Youth Development Programs Targeting Students with Greater Psychosocial Needs: Subjective Outcome Evaluation - Daniel T. L. Shek; Tak Yan Lee; Rachel C.F. Sun; Daniel W.M. Lung (The Scientific World Journal)
The Tier 2 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) targets adolescents with greater psychosocial needs, and the related programs were designed and implemented by school social workers. After completion of the Tier 2 Program, 2,173 students in 52 schools responded to the Subjective Outcome Evaluation Form (Form C), assessing their views of the program, instructors, and perceived effectiveness of the program. Based on the consolidated reports submitted by the agencies to the funding body, the research team aggregated the consolidated data to form a “reconstructed” overall profile of the perceptions of the program participants. Four major types of program were identified, including programs based on the adventure-based counseling approach (N = 8), programs concentrated on volunteer training and services (N = 7), programs incorporating both adventure-based counseling and volunteer training elements (N = 30), and other programs with different foci (N = 7). Results showed that high proportions of the respondents had positive perceptions of the programs and the instructors, and roughly four-fifths of the respondents regarded the program as helpful to them. The present study provides support for the effectiveness of the Tier 2 Program of P.A.T.H.S. in Hong Kong for the experimental implementation phase.